Strain distribution on a finger link: a static simulation study. (19th May 2018) - Liu, Jiawen; Chappell, Paul; White, Neil
Abstract: Functional prosthetics hands which have the ability to help amputees perform tasks in daily life have been developed over many years. These hands need a control system which is fed information from sensors mounted on a prosthetic hand and human–machine interface. A variety of sensors therefore been developed for the prosthetic hand to measure fingertip force, joint angle (position), object slip, texture and temperature. However, most of the strain/stress sensors are attached to the fingertip. In this paper, the potential positions for strain sensors on the side of the finger link of the prosthetic hand are investigated that, in the future, will allow for force control in a lateral or key grip. With modified links of a Southampton Hand, some promising positions for strain sensors have been determined. On some of the links, the strain sensor can be used as an indicator to show the angle of the finger during a curling operation.